Efficacy and safety of the anticoagulant drug, danaparoid sodium, in the treatment of portal vein thrombosis in patients with liver cirrhosis. Issue 6 (2nd September 2014) - Naeshiro, Noriaki; Aikata, Hiroshi; Hyogo, Hideyuki; Kan, Hiromi; Fujino, Hatsue; Kobayashi, Tomoki; Fukuhara, Takayuki; Honda, Yohji; Nakahara, Takashi; Ohno, Atsushi; Miyaki, Daisuke; Murakami, Eisuke; et al.
<x xml:space="preserve">Abstract</x> Aim To assess the efficacy and safety of the anticoagulant drug, danaparoid sodium, in the treatment of portal vein thrombosis (PVT) in patients with liver cirrhosis. Methods A consecutive 26 cirrhotic patients with PVT were enrolled in this retrospective cohort study. The etiologies of cirrhosis were hepatitis B virus‐related, hepatitis C virus‐related, alcoholic and cryptogenic in five, 14, three and four patients, respectively. Child–Pugh grade A, B and C was noted in 13, eight and five patients, respectively. Patients were treated with 2 weeks' administration of danaparoid sodium followed by the evaluation of PVT reduction and adverse events. Results All patients experienced reduction of PVT through the treatment. The median volume of PVT before and after treatment was 2.40 cm3 (range, 0.18–16.63) and 0.37 cm3 (range, 0–5.74), respectively. The median reduction rate of PVT volume was 77.3% (range, 18–100%). According to the reduction rate, complete reduction (CR), partial reduction (PR, ≥50%) and stable disease (SD, <50%) were observed in four (15%), 16 (62%) and six patients (23%), respectively. The median volume of PVT before treatment was significantly different between CR + PR and SD (2.09 vs 4.35 cm3, P = 0.045). No severe adverse events such as bleeding symptoms (e.g. gastrointestinal bleeding and cerebral hemorrhage) and thrombocytopenia were encountered. Conclusion Danaparoid sodium for the treatment of PVT in patients with liver cirrhosis was safe and effective. Therefore, anticoagulation therapy with danaparoid sodium could have potential as one of the treatment options in PVT accompanied by cirrhosis.